Genetic analysis of zinc, iron and provitamin A content in tropical maize (Zea mays L.) - Udo, E.; Abe, A.; Meseka, S.K.; Mengesha Abera, W.; Menkir, A. (MDPI, 2023)
Breeding maize with high contents of zinc, iron and provitamin A (PVA) could be effective in mitigating micronutrient deficiency in developing countries with a high reliance on maize-based diets. Information on the mode of inheritance of zinc, iron, PVA and grain yield (GY) would facilitate the development of varieties with enhanced contents of these nutrients. Twenty-four yellow to orange maize inbred lines and their 96 F1 hybrids generated using North Carolina Design II, were evaluated alongside four checks for two years at two locations in Nigeria. The effects of environment, hybrid and inbred line were significant for GY and contents of zinc, iron and PVA. The GY, and contents of zinc, iron and PVA of the hybrids ranged from 1.49 to 6.05 t ha−1, 22.51 to 33.33 mg kg−1, 20.04 to 29.65 mg kg−1 and 3.55 to 15.28 µg g−1, respectively. Additive gene effects controlled the accumulation of PVA and Fe, whereas both additive and non-additive gene effects controlled the inheritance of Zn and GY. Inbred lines with high general combining ability for GY and single or multiple micronutrients were identified, and could be used to develop hybrids and synthetics that combine high GY with high micronutrient content. Six hybrids combined high GY with high contents of all three micronutrients, and are recommended for further evaluation and possible release. Our study revealed the feasibility of enriching maize with multiple micronutrients without compromising grain yield.